Penegakan Hukum terhadap Pertambangan Tanpa Izin Menurut Undang-Undang Nomor 4 Tahun 2009 tentang Pertambangan Mineral dan Batu Bara - Reggy Rahadian Taufiqurahman (Savana, 2024)
This study aims to understand the law enforcement process related to illegal mining activities and whether business actors involved in these activities receive legal protection or assistance from the government when facing problems. Using a normative legal research method, this study concludes that: 1. Law enforcement against illegal mining activities as regulated in Law Number 4 of 2009 concerning Mineral and Coal Mining is carried out through three legal areas: Administrative, Civil, and Criminal Law Enforcement. 2. Business actors conducting illegal mining activities, when facing problems related to their mining activities, whether with the surrounding community or with other mining companies, will not receive legal assistance in resolving them. However, these business actors will still receive legal protection from the local and central governments.